2014
DOI: 10.1002/dc.23237
|View full text |Cite
|
Sign up to set email alerts
|

Strategic management of transthoracic needle aspirates for histological subtyping and EGFR testing in patients with peripheral lung cancer: An institutional experience

Abstract: We hereby proposed a strategy to maximize biological information retrieval from a limited TTNA specimen in patients with peripheral lung cancer. This algorithm indicated CB preparation for accurate histological subtyping and waste needle washing for molecular testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this study, we did not explore the minimum cells volume for EGFR mutations analysis. One study indicated that even 100–1,000 tumor cells from FNA samples provided reliable results of mutations analysis when sensitive real time PCR method was used [ 16 ]. Another study indicated that the cytological sample with low (10–20%) content of tumor cells was also a sufficient source for EGFR mutation testing in NSCLC patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not explore the minimum cells volume for EGFR mutations analysis. One study indicated that even 100–1,000 tumor cells from FNA samples provided reliable results of mutations analysis when sensitive real time PCR method was used [ 16 ]. Another study indicated that the cytological sample with low (10–20%) content of tumor cells was also a sufficient source for EGFR mutation testing in NSCLC patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence base for this statement comprises 5 studies 41,60,[79][80][81] that evaluated diagnostic yield and adequacy outcomes based on number of passes, 2 studies 41,60 reporting on adverse events of multiple passes, and 8 studies 59,[82][83][84][85][86][87][88] reporting on diagnostic yield and adequacy when a tissue block was created. The aggregate risk of bias across the 13 studies was very serious.…”
mentioning
confidence: 99%
“…All studies 41,60,[79][80][81] reporting on diagnostic outcomes suffered from risk of bias in relation to patient selection, 4 studies 41,60,79,80 were limited by detection bias, 4 studies 41,60,79,81 contained missing data, and 2 studies 41,79 did not report on funding source. Of the 8 studies reporting on the creation of tissue blocks, 3 were prospective cohort studies 59,84,87 and 5 were retrospective cohort studies. 82,83,85,86,88 Included studies were limited by their risk of bias in relation to patient selection, 59,[82][83][84][85][86][87][88] performance, 59,85 detection, 59,83,[85][86][87][88] and reporting, 59,[83][84][85][86][87] as well as a lack of reported funding.…”
mentioning
confidence: 99%
See 2 more Smart Citations